Youth Leadership Character Development at the Karang Taruna Organization in Karawang West Java - Very Sukma Firmansyah; Encep Syarif; Yadi Ruyadi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study discusses the role of the Karang Taruna Organization Leader in Karawang Regency in building youth character. This study used descriptive qualitative method. Data collection techniques used 5 techniques, namely in-depth interviews, observation, internet, and literature study. The process of data analysis in this study, namely data collection, data reduction, data presentation, and drawing conclusions. The results of research in the field show that the role of the Karang Taruna Organization Leader in Karawang Regency can build the character of youth, but it cannot be maximized because there are several obstacles, namely finance, lack of coordination of the management, lack of activeness of the board and personal interests. The characters that can be built in the organization are religious, responsible, disciplined, independent, honest, trustworthy, caring for others, cooperation, self-confidence, creativity, never giving up, leadership, tolerance, and nationalism. The role of the Leader of the Karang Taruna Organization in Karawang Regency can have implications for the personal resilience of youth, especially Basic Education and Training, because other activities are not running effectively. The implications of basic education and training can build an independent personality, togetherness, self-confidence, sticking to principles, dynamic, creative, and never give up. especially basic education and training, because other activities are not running effectively. The implications of basic education and training can build an independent personality, togetherness, self-confidence, sticking to principles, dynamic, creative, and never give up. Especially basic education and training, because other activities are not running effectively. The implications of basic education and training can build an independent personality, togetherness, self-confidence, sticking to principles, dynamic, creative and never give up.